Case Study: Road Safety Inspection Along Federal Route FT23 in Bandar Tangkak Using Unmanned Aerial Vehicle - Dominick Andy Amry; Haikal Hadie; Azurah Ismail; Mohd Erwan Sanik (Multidisciplinary Applied Research and Innovation, 2026)
Road safety remains a critical concern, particularly for vulnerable road users (VRUs) such as pedestrians and motorcyclists. This study examines road safety along Federal Route FT23 in Bandar Tangkak using Unmanned Aerial Vehicle (UAV) technology in accordance with MeTRA framework and Stage 5 Audit standards. UAVs offer a modern alternative to traditional inspection methods, providing detailed evaluations of road infrastructure and user behavior. UAVs improve inspections by providing safer access to hard-to-reach areas, reducing the need for scaffolding or lane closures. They capture high-resolution images and real-time data quickly and accurately, allowing for faster, cost-effective and detailed assessments. This enhances safety, efficiency and decision-making in industries like construction, infrastructure and disaster response. This study aims to improve interventions such as exclusive motorcycle lanes, maintained sidewalks, improved pedestrian crossings and continuous monitoring using UAVs.